Genome-wide characterization of heavy metal-associated isoprenylated plant protein gene family from Citrus sinensis in response to huanglongbing - Huang, Guiyan; Hu, Yanan; Li, Fuxuan; Zuo, Xiru; Wang, Xinyou; Li, Fengyao; Li, Ruimin (Frontiers in Plant Science, 2024)
Heavy metal-associated isoprenylated plant proteins (HIPPs) play vital roles in maintaining heavy metal balance and responding to both biotic and abiotic stresses in vascular plants. However, the role of HIPPs in the response to Huanglongbing (HLB), a harmful disease of citrus caused by the phloemcolonizing bacterium Candidatus Liberibacter asiaticus (CLas), has not been examined. In this study, a total of 26 HIPP genes were identified in Citrus sinensis, and they were grouped into 5 clades. The CsHIPP genes are distributed on 8 chromosomes and exhibited considerable synteny with HIPPs found in Arabidopsis thaliana. Additionally, we analyzed the gene structure, conserved motifs and domains of the CsHIPPs. Various cis-acting elements related to plant hormones and stress responses were identified in the promoters of CsHIPPs. Public transcriptome data and RT-qPCR analysis showed that the expression level of CsHIPP03 was significantly reduced in samples infected by CLas and Xanthomonas citri ssp. citri (Xcc). Furthermore, silencing the homologous gene of CsHIPP03 in Nicotiana benthamiana increased the disease resistance of plants to bacteria. Our results provide a basis for functional studies of HIPP gene family in C. sinensis, highlighting their functions in bacterial resistance, and improve our understanding to the susceptibility mechanism of HLB.